Religion’s Elements and Social’s Conflict in “Mata yang Enak Dipandang” by Ahmad Tohari: Research of Sociology of Literature - Hariyadi, Muhamad; Mardikantoro, Hari Bakti (Pascasarjana Universitas Negeri Semarang, 2018)
This research examines the religious and social conflicts in the short story’s collection “Mata yang Enak Dipandang” by Ahmad Tohari. The religious theme does not only focus on religious ritual practices but penetrates universal religious elements. In addition to religious themes, social conflict is used as a theme in this collection of short stories. The problems studied are forms of religious elements, depictions of social conflict, the relationship between religious elements and social conflicts in short stories’ collection “Mata yang Enak Dipandang”. The purpose of the research is to describe the elements of religion, social conflict, and the relationship between religious elements and social conflict. This research is carried out with the sociology of literature using the study of hermeneutics. Data research is in the form of words, phrases, and sentences contained in fragments of short stories containing religious elements and social conflicts contained in short stories“Mata Yang Enak Dipandang”.Religious elements in this short stories’ collection include religious emotions, belief systems, and ritual systems and ceremonies. Existing social conflicts are individual conflicts with individuals, inner conflicts, and individual conflicts within groups. The relationship between religious elements and social conflicts, namely the religious element is used as a view of life and reference in resolving social conflicts. We recommend that actions taken must be sourced from religious values in order to minimize the occurrence of social conflicts, so as to create a life of peace and harmony in the community.